2015
DOI: 10.1007/s10856-015-5470-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of total knee replacements with UHMW-PE inserts: impact of severe wear test conditions

Abstract: Aseptic implant loosening due to inflammatory reactions to wear debris is the main reason for the revision of total knee replacements (TKR). Hence, the decrease in polyethylene wear particle generation from the articulating surfaces is aimed at improving implant design and material. For preclinical testing of new TKR systems standardized wear tests are required. However, these wear tests do not reproduce the entire in vivo situation, since the pattern and amount of wear and subsequent implant failure are under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 89 publications
0
20
0
Order By: Relevance
“…However, it has been shown that variation in the experimental conditions, such as kinematic inputs and component alignment, will have an impact on the wear performance of a TKR. 10,[14][15][16] Indeed, different research centres have adopted different approaches to experimental wear simulation of TKRs, with different conditions all too common. The resulting contact point movement that these simulations produce will depend on the combination of many parameters including input displacement magnitudes, waveforms, direction of motion and femoral centre of rotation (CoR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that variation in the experimental conditions, such as kinematic inputs and component alignment, will have an impact on the wear performance of a TKR. 10,[14][15][16] Indeed, different research centres have adopted different approaches to experimental wear simulation of TKRs, with different conditions all too common. The resulting contact point movement that these simulations produce will depend on the combination of many parameters including input displacement magnitudes, waveforms, direction of motion and femoral centre of rotation (CoR).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that variation in the experimental conditions, such as kinematic inputs and component alignment, will have an impact on the wear performance of a TKR. 10,1416…”
Section: Introductionmentioning
confidence: 99%
“…Charnley preserved with polymer on metal combinations to maintain low frictional torques and introduced UHMWPE cups sliding on stainless steel femoral heads. This combination of materials has proved to be extremely successful giving low friction, low wear rates of the UHMWPE and smaller amounts of wear debris, which could be more readily tolerated by the body [10,11,20,21].…”
Section: Frictionmentioning
confidence: 99%
“…Some of the sources of experimental variability include the choice of displacement vs force control (Schwenke et al, 2009), differences in the lubricant (Brandt et al, 2010;Schwenke et al, 2005;Wang et al, 2004), the component starting position (Cheng et al, 2003;Zietz et al, 2015), and the effect of fluid absorption by the polyethylene, which can mask low wear rates (Schwenke et al, 2005). Another source of variability within TKR wear tests that has been identified is the definition of the femoral flexion/extension center of rotation (CoR) (Brockett et al, 2016;DesJardins and Rusly, 2011;Jennings et al, 2007;McEwen et al, 2005;Zietz et al, 2015). The location of femoral CoR location is also clinically relevant, as its position can vary surgically (Abdel et al, 2014;Rivière et al, 2017).…”
Section: Introductionmentioning
confidence: 99%